T-cell depletion with Campath-1H "in the bag" for matched related allogeneic peripheral blood stem cell transplantation is associated with reduced graft-versus-host disease, rapid immune constitution and improved survival. - Chakrabarti, S; MacDonald, D; Hale, G; Holder, K; Turner, V; Czarnecka, H; Thompson, J; Fegan, C; Waldmann, H; Milligan, D (2003)
We studied the outcome of 24 peripheral blood stem cell (PBSC) graft recipients, who were T-cell depleted (TCD) with either 20 mg (n = 14) or 10 mg (n = 10) Campath-1H in vitro, in comparison with a retrospective cohort of 23 unmanipulated (UM) PBSC recipients. While the neutrophil engraftment was similar, the platelet engraftment occurred earlier in the TCD group (d 11 vs 14). The incidence of acute and chronic graft-versus-host-disease (GVHD) was 8.7% and 4.4% in the TCD group, respectively, compared with 47.7% and 56.3% in UM group (P < 0.001). In the TCD group, 5/6 chronic myeloid leukaemia (CML) and 4/18 non-CML patients relapsed (vs 0/6 and 3/17 in UM group, P = 0.06). All four molecular or cytogenetic relapses of CML were disease-free survivors following donor lymphocyte infusion. There was no difference in the incidence of serious infection between the TCD and UM groups and the lymphocyte recovery at 100 d was comparable. In the TCD cohort, the lymphocyte recovery was quicker in the 10 mg Campath-1H group. The non-relapse mortality (19.1%vs 66.3%) and 3 year survival (73.1 vs 19.2) were improved in the TCD group (P = 0.05). Thus elimination of late mortalities related to chronic GVHD and a rapid immune reconstitution, limiting either infection or relapse related deaths, contributed to an improved outcome following T-cell depletion with Campath-1H "in the bag".